Yolk Sac Tumor of the Ovary in Mosaic 46XX Turner Syndrome - Suryawan AZ; Tjahyadi D; Hermawan M; Aprialdi D (Dove Medical Press, 2024)
Alfonsus Zeus Suryawan, Dian Tjahyadi, Martin Hermawan, Doni Aprialdi Department of Obstetrics and Gynecology; Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Alfonsus Zeus Suryawan, Department of Obstetrics and Gynecology, Universitas Padjadjaran, Hasan Sadikin General Hospital, Jalan Pasteur No. 38, Bandung, 40161, Indonesia, Email alfonsus21001@mail.unpad.ac.idIntroduction: Correlation of Turner syndrome (TS) with germ cell malignancy is acknowledge in TS patient with Y chromosome material but not otherwise. This case report wishes to highlight yolk sac tumor occurrence in patients with TS 46XX karyotype mosaicism.Case Report: A 23-year-old nulligravid woman was admitted with abdominal mass and vaginal bleeding. She had primary amenorrhea and had already been diagnosed with TS. Her karyotype was 46XX with 5% X mosaicism. Ultrasonography revealed a solid mass measuring 14.05 x 10.99 cm based on the International Ovarian Tumor Analysis (IOTA) simple rule, M1 and M2. During surgery, a solid mass originates from her left ovary measuring 20 x 15 x 15 cm with adhesion to omentum, ileum, and caecum was found. Pathology examination reveals it's an endodermal sinus tumors (EST).Discussion: TS with Y cells are closely linked with germ cell malignancy but not otherwise. It's still unclear what causes the malignancy in such cases.Conclusion: The present report illustrates a rare case of EST occurred in a TS patient with 46XX mosaicism.Keywords: Turner syndrome, endodermal sinus tumor, yolk sac malignancy, mosaicism, 46XX karyotype